Water-pH phytoremediation: An entrance to exploiting the potential of plant biomass ash in water defluoridation - Hezron Timothy Mwakabona-NjauKaroli N- BruggenBart Van der (University of Eloued جامعة الوادي, 2024)
Field application of low-cost biomass ash in water defluoridation is hindered by media-induced contamination in the treated water including pH elevation. This study explored the method for adjusting pH of water using Cyperus plants. Findings reveal that used ash material is calcium rich with concentration of 537.9 gKg-1. The ash water extract was found to be rich in K with concentration of 642.6 gKg-1. The ash material used was found to have faster and sustained fluoride removal, attaining 76% removal efficiency in 30 minutes with slow increase throughout the experimental time of 24 hours. The pH of the ash-defluoridated water was found to increase from 8.3 to an average of 12.2. Live Cyperus plants showed ability to lower the pH of the treated water from 12.2 to 7.3 and elevate the pH of acid treated water from 3.5 to 6.8. This implies that these plants exude some form of buffer compounds with a constant pH of around 7. This was confirmed by concentration of hydrogencarbonates was found to increase while that of the carbonates decreased in the Cyperus-treated water. This could further imply that the Cyperus-assisted pH adjustment is effected by a buffer compound released by these plants.
Article
Keywords: Defluoridation; Cyperus spp; Biomass ash